Protective and decorative coatings : raw materials, pigments, metallic powders, and metallic soaps - Mattiello, Joseph J. (Wiley)
Contiene: Classification, chemistry, microscopic identification, and particle size; Colored pigments; White hiding pigments; White extender pigments; Black pigments; Metallic powders; Metallic soaps.